Influence of type of aluminium stearate on triboelectrification of dry-coated surfaces of functionalised glass beads - Goh, Wei Pin; Guo, Jiachen; Jia, Xiaodong; Ghadiri, Mojtaba (Frontiers in Chemical Engineering, 2024)
Triboelectrification of powders and grains is deleterious in a large number of manufacturing operations, due to its adverse effect on process consistency and reliability. To mitigate it, charge neutralisers are commonly employed. However, their selection is often based on trial and error. This study is conducted to systematically examine the influence of the ionic polarity strength of a charge neutraliser, specifically aluminium stearate (AlSt), on charge transfer. AlSt has three types with different numbers of stearate chains, thereby influencing the electron exchange propensity of the molecule. The experiments involved surface-treated glass beads in the sieve size range of 90-150 µm (to make them hydrophilic by acid washing or hydrophobic by silanisation), then coated with the three forms of AlSt (mono-, di- and tri-) for charge mitigation. These coated beads were subjected to aerodynamic dispersion to cause triboelectrification, in order to quantitatively evaluate their charge neutralising effect. The experiments were conducted with four contact surfaces: stainless steel, copper, aluminium, and polytetrafluoroethylene (PTFE). Both acid-washed and silanised glass beads exhibited negative charging against aluminium, copper and stainless steel (typically around 22-44 nC/g), but positive charging against PTFE (around 90 nC/g and 19 nC/g for acid-washed and silanised, respectively), despite having significantly different surface functional groups. A complex trend is observed for the effect of the amount of AlSt present on the surfaces, the type of AlSt and the surface treatment. A relatively good charge reduction behaviour was seen for AlSt-coated acid washed glass beads, but for silanised glass beads, coated by AlSt actually increases their charge level.